(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
The historic collection of fossil odontocetes (Cetacea) from Monte Voltraio, near Volterra (Tuscany, Italy) has been examined and lithostratigraphical and biostratigraphical investigations on the find locality have been carried out. The Monte Voltraio outcrop is referred to the Middle Pliocene, in particular to Globorotalia aemiliana and Discoaster tamalis zones. The odontocete remains are assigned to the families Kogiidae (Kogia pusilla) and Delphinidae (Globicephala? etruriae and two indeterminate specimens which might belong to Hemisyntrachelus and Stenella giulii). The Middle Pliocene cetacean fauna from the Mediterranean basin (Monte Voltraio and Rio Stramonte associations) includes extinct taxa or extant taxa no longer represented in this basin. The disappearance of these taxa may be linked with the Pliocene and/or Quaternary climatic deteriorations (e.g. the climatic crisis at about 2.6-2.4 MA).